ENHANCING CALLUS FORMATION IN TAPAKTUAN PATCHOULI THROUGH IN VITRO OPTIMIZED COMBINATIONS OF PGR - Alya Munira; Khairan Khairan; Sreeramanan Subramaniam; Essy Harnelly (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlight - Different varieties of Patchouli exhibited different growth pattern as well as in vitro culture - In order to induce callus, it has been determined that the combination of regulators is necessary. - Benzylaminopurine has been identified as a potential regulator that could be used to further develop the patchouli callus of Tapak Tuan.